2020
DOI: 10.1177/0961203320932219
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus, lupus nephritis and end-stage renal disease: a pragmatic review mapping disease severity and progression

Abstract: Objective The understanding of systemic lupus erythematosus (SLE) and lupus nephritis (LN) pathogenesis remains incomplete. This review assessed LN development in SLE, within-LN progression and progression to end-stage renal disease (ESRD). Methods A keyword-based literature search was conducted, and 26 publications were included. Results Overall, 7–31% of patients had LN at SLE diagnosis; 31–48% developed LN after SLE diagnosis, most within 5 years. Class IV was the most commonly found LN class and had the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 47 publications
2
99
0
7
Order By: Relevance
“…In cSLE populations, decreased creatinine clearance rate and low C3 complement levels with high serum creatinine levels were associated with end-stage renal disease [ 169 ]. A recent study, including 26 previous reports, showed that high serum creatinine (> 1.5 mg/dL) at disease presentation was the major prediction factor for progression to end-stage renal disease [ 170 ]. Furthermore, high titers of anti-dsDNA antibodies have modest accuracy to predict lupus nephritis [ 171 ].…”
Section: Csle Prognosis Factorsmentioning
confidence: 99%
“…In cSLE populations, decreased creatinine clearance rate and low C3 complement levels with high serum creatinine levels were associated with end-stage renal disease [ 169 ]. A recent study, including 26 previous reports, showed that high serum creatinine (> 1.5 mg/dL) at disease presentation was the major prediction factor for progression to end-stage renal disease [ 170 ]. Furthermore, high titers of anti-dsDNA antibodies have modest accuracy to predict lupus nephritis [ 171 ].…”
Section: Csle Prognosis Factorsmentioning
confidence: 99%
“…Approximately 31-48% of patients with SLE develop lupus nephritis (LN), the most severe organ manifestation of SLE, with 7-31% of patients being diagnosed with LN at SLE diagnosis [4][5][6][7]. Patients with LN have a higher risk of death compared with the general population, a risk that increases further if LN progresses to end-stage kidney disease (ESKD) [8].…”
Section: Introductionmentioning
confidence: 99%
“…This condition has now become a global public health problem. IgA nephropathy (IgAN) and lupus nephritis (LN) is the most common primary and secondary glomerular diseases, respectively, and tend to affect young adults, with nearly 20% of patients progressing to ESRD after 10 years because of limited drug treatment options ( Mahajan et al, 2020 ; Natale et al, 2020 ). Although both diseases have complex and varied clinical manifestations, many overlaps have been noted.…”
Section: Introductionmentioning
confidence: 99%